The role of the ward committees as an interface between local government and community: a case study of Makana Municipality - Stuurman, Sonwabo Happyboy (Rhodes University, Faculty of Humanities, Department of Sociology, 2009)
The Ward Committee System was introduced in South Africa in 2001 as a tool to bring government closer to the people and to enhance participatory democracy. The Makana Municipality adopted the system in 2002. Previous research on local government indicates that these structures have not been effective due to the lack of resources to sustain them. This study was interested in furthering such research, using the Makana Municipality as a case study during which unstructured, in-depth interviews and focus group discussions were conducted with Ward Councillors, Ward Committee Members and Grade 12 learners. The aim of the research was to investigate whether the ward committees did indeed promote the notion of participatory democracy and to what extent grass roots development has been enhanced by this structure of local government. The findings from both the respondents and the observations indicate that, in addition to the lack of resources, the underutilization of the Ward Committee System is a result of the effect of opposing political affiliations within the ward committee system, affiliations that undermine the goal of collaborative decision-making. Whereas the ward committee system is a positive idea, the findings suggest that the government is not supporting these structures by failing to equip the ward committee members with necessary capacities and skills. Therefore, if municipalities are committed to bridging the gap between local government and the community, and are keen to enhance participatory democracy, then capacity building of the ward committees and respect for their role during the decision-making process need to be taken seriously. At present, ward committee members are not influential and active in the decision-making process. In addition, the youth as prospective future ward committee members seemed disillusioned with the notion of participatory democracy, and instead have adopted the mentality that nepotism and corruption, as displayed by those in power, is the only way of governance. This research suggests that the ward committee system, intended to bring government closer to the people, may in fact not only alienate government from the people, but also the people from each other.
Keywords: Makana Municipality; Local government -- South Africa -- Case studies; Local government -- South Africa -- Citizen participation; Community development -- South Africa -- Case studies; Political participation -- South Africa -- Case studies; Democracy -- South Africa; South Africa -- Politics and government -- 1994-; South Africa -- Politics and government -- 21st century